2020
DOI: 10.1155/2020/6641461
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antibiotic Resistance-Coliform Bacteria in Some Selected Fish Farms of the Central Region of Ghana

Abstract: This study aimed at assessing the quality of water and fishery products as well as the antibiotic resistance status of some selected fish farms of the Central Region of Ghana. Interview guides were administered to farmers to get data on farming practices and antibiotic use. Total coliform loads of catfish (Clarias gariepinus), tilapia (Oreochromis niloticus), and water samples were determined. Coliforms were identified through various biochemical assays, and their antibiotic resistance patterns were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…An assessment of AMR in tilapia and catfish farms in Ghana found that out of 63 coliform bacteria tested, the majority were resistant to ampicillin (98.4%), cefuroxime (88.9%), tetracycline (66.7%), cefotaxime (52.4%), and co-trimoxazole (56.0%). Of the eight tested antimicrobials, gentamicin was the only effective drug (6.4%) [ 100 ]. A previous study on isolates from tilapia and catfish farms in Ghana reported that all S. aureus isolates exhibited 100% resistance to penicillin, ampicillin and flucloxacillin.…”
Section: Resultsmentioning
confidence: 99%
“…An assessment of AMR in tilapia and catfish farms in Ghana found that out of 63 coliform bacteria tested, the majority were resistant to ampicillin (98.4%), cefuroxime (88.9%), tetracycline (66.7%), cefotaxime (52.4%), and co-trimoxazole (56.0%). Of the eight tested antimicrobials, gentamicin was the only effective drug (6.4%) [ 100 ]. A previous study on isolates from tilapia and catfish farms in Ghana reported that all S. aureus isolates exhibited 100% resistance to penicillin, ampicillin and flucloxacillin.…”
Section: Resultsmentioning
confidence: 99%
“…In most African countries, especially Ghana, the indiscriminate use of antibiotics in fish culture is of grave public health concern due to the development of multiple‐antibiotic resistance in many aquatic bacterial pathogens (Adinortey et al. 2020). The resistance of the isolate A. jandaei GH‐AS II to tetracycline and ampicillin as found in this study was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The unregulated use of antibiotics in fish production in Ghana could limit international trading opportunities. There is dearth of information on the misuse of antibiotics even though there are wide reports on their use in Ghana's aquaculture industry (Adinortey et al., 2020; Agoba et al., 2017; Donkor et al., 2018; Nkansa, 2017). Owing to the use of antibiotics in Ghana's aquaculture industry, acquiring knowledge on the reasons for their usage can be useful in finding alternative treatments or remedial measures.…”
Section: Methodsmentioning
confidence: 99%